TAX COMPONENT OF FISCAL POLICY OF INCREASE COMPETITIVENESS OF NATIONAL ECONOMICS - Danilov О.Д. (Journal of Information Technologies in Education (ITE), 2014)
The article is devoted to the problems of using fiscal levers to regulate the national economy competitiveness. What kind of tax levers should be used in order to increase the competitiveness of the national economy is justified. Taxes are the main source of fiscal revenue of the country, which depends on the inherent principles of optimizing the tax system, determined Ukraine’s withdrawal from the crisis and raising the country’s competitiveness. It is proposed differentiation in income tax rates, depending on whether the company is engaged in innovation and investment activity or not. Changing the rate of value added tax in a downward will reduce the revenue of the country.For enterprises that are not exporting products to decrease the amount of working capital for a certain period Fiscal policy that promotes the removal of the country’s financial and economic crisis and the increasing competitiveness of the state, should be challenging. In order to implement incentive effects of taxes set forth in the tax code, we propose a linear programming model of the budget (revenue and expenditure). Building the economic and mathematical optimization model with possible actions challenging the tax factors of individual taxes and the possibilities of using the proceeds of certain taxes on certain items of expenditure budget.